PEMBANGUNAN APLIKASI TASK MANAGEMENT DALAM MENDUKUNG PROYEK PENGEMBANGAN PERANGKAT LUNAK (STUDI KASUS : PT. eBDESK INDONESIA) - Fauzan, Rauf; Nugraha, Irpan Bangga (JUTEI (Jurnal Terapan Teknologi Informasi) (Online), 2017)
Scheduling on tasks and an employee arrangements in the field is extremely important, due to the continuous increase task. Schedulling an employee in the field today is considered very weak, this can be inferred from the number of an employee who are unable to take advantage of the time given a company to finish the job. Task Management Web-Based Applications Using PHP and MySQL as a tool to support the process of scheduling and field arrangements and is expected to be the ground control an employee in carrying out their duties In this Final Project, the author wants to build a web-based management application using PHP programming language and MySQL database. Which is expected to provide convenience to an organization in doing the scheduling.